Novel bio-functional architectures of polymersomes - Siti, Winna (2015)
Cell, as a source of inspiration, is a key functional unit of living organism. Its interior consists of different structures composed of soft matter that are highly selective and functions with different roles. Compartmentalization is one of the main features of eukaryotic cells, giving organelles to achieve some essential functions, such as protein synthesis, replication and energy production within close proximity. With the purpose to mimic cellular compartments, lots of model systems based on lipids (liposomes) or polymers (polymersomes) have been developed. Polymersomes (also known as polymer vesicles) are spherical nanostructured entities with a hollow aqueous compartment enclosed by a bilayer membrane of synthetic amphiphilic block copolymers. Compared to the traditionally used liposomes, they have several properties which make them especially suited for lots of applications in biomedicine and biotechnology. Amongst others, their superior stability and excellent chemical diversity allowing their properties of its membranes to be tuned (e.g. selective permeability). Here, the thesis covers two parts of research work and the focus of the study is to use polymersomes system with specific functionality to build novel architectures for mimicking the complexity of living cells.